Spin-lattice coupling and frustrated magnetism in Fe-doped hexagonal LuMnO3. (19th May 2015) - Nair, Harikrishnan S.; Fu, Zhendong; Kumar, C. M. N.; Pomjakushin, V. Y.; Xiao, Yinguo; Chatterji, Tapan; Strydom, André M.
Abstract: Strong spin-lattice coupling and prominent frustration effects observed in the 50% Fe-doped frustrated hexagonal are reported. A Néel transition at and a possible spin re-orientation transition at are observed in the magnetization data. From neutron powder diffraction data, the nuclear structure at and below 300 K was refined in polar P 63 cm space group. While the magnetic structure of LuMnO3 belongs to the representation, that of LuFe0.5 Mn0.5 O3 belongs to which is supported by the strong intensity for the (100) reflection and also judging by the presence of spin-lattice coupling. The refined atomic positions for Lu and Mn/Fe indicate significant atomic displacements at and which confirms strong spin-lattice coupling. Our results complement the discovery of room temperature multiferroicity in thin films of and would give impetus to study LuFe1− x Mn x O3 systems as potential multiferroics where electric polarization is linked to giant atomic displacements.